Technical means for mechanization of technological processes on livestock farms - Skliar, Oleksandr; Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Grigorenko, Serhii; Григоренко, Сергій Михайлович; Григоренко, Сергей Михайлович; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (My University, 2021)
One of the reasons hindering the development of animal husbandry in an innovative way is the lack of a promising program of technical and technological equipment, programs for the creation and production of machinery, programs for the development of specialized engineering for animal husbandry and feed production. In Ukraine, there are no specialized plants for the production of innovative equipment, the destroyed base of repair and technical service and the system of training of engineering personnel for animal husbandry. Regional and regional management bodies of the agricultural sector do not implement technical policy in the field of mechanization and automation of animal husbandry. Restoration and development of the domestic base of agricultural machinery for animal husbandry should be carried out on the basis of a promising program of mechanization and automation of the industry, which includes promising resource-saving production technologies and technologies for processes and operations.
Keywords: animal husbandry; technological equipment; feed production; mechanization; resource-saving production technologies